Sexually Harassment In Boarding Schools And Universities - Haitsam; Finkan; Intan; Aditia; -, Alfina (Universitas Nahdlatul Ulama Sunan Giri, 2023)
Acts of sexual harassment against women are referred to as sexual harassment, regardless of whether the victim and perpetrator had sexual intercourse or not. Islamic boarding schools have the second highest rate of sexual violence after universities, even though universities and Islamic boarding schools play an important role in the development of individual character and identity. These locations are still considered unsafe for women and children, as evidenced by sexual harassment. Islamic boarding schools and universities that should be places for people to study have turned into places where teachers, administrators, and even ustadz can get what they want. These individuals usually rely on religious doctrine or even be lured by financial content to obtain various educational guarantees, such as being given high marks or questions that have been leaked. This research examines cases of sexual harassment that occurred in Islamic boarding schools and universities, provides an overview of the steps taken to address and prevent such incidents, and evaluates the extent to which these steps have been successful. This study uses a descriptive qualitative method, which aims to accurately and methodically describe the facts and characteristics of a population or a particular field. It is hoped that this research will be able to describe various problems related to sexual harassment faced by female students and students at universities or Islamic boarding schools. Sexuality education and awareness must be implemented immediately. This is a key reason for a deeper look into demonstrations of sexual brutality and how to protect oneself from sexual violence and perspectives on managing sexual violence. All stakeholders, including students, teachers, education staff, and the campus community, must participate in this introduction.